Iron in polish female soccer players - dietary intake and questionnaire validation - Dobrowolski, H.; Wlodarek, D. (Science & Sports, 2020)
Objectives: The aim of the study was to evaluate dietary iron intake by professional female soccer players and to estimate the possible risk of iron deficiency.